K-Region-Extended [c]-Heteroannulated Pyrenes - Baumgärtner, Kevin; Kirschbaum, Tobias; Krutzek, Fabian; Dreuw, Andreas; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2017)
Extended fused aromatic compounds are promising materials for organic electronics. Among them, structures with five-membered annulated rings differ from those consisting only of six-membered carbocyclic rings. To date, fusion of five-membered rings has been realized mainly via the [b]-edge, and systems fused via the [c]-edge are of low stability. Whereas linearly double [b]-fused systems are stable, analogous [c]-fused systems have not been described to date. Comparable to the stabilization of longer acenes by peri-fusion, herein the synthesis of doubly [c]-annulated systems stabilized by double peri-fusion is described. The compounds were analyzed by X-ray crystallography, photophysical methods, and DFT calculations to gain deeper insight into the nature of conjugation in these new systems.